Advances in Biofuels and Bioenergy 2018
DOI: 10.5772/intechopen.73304
|View full text |Cite
|
Sign up to set email alerts
|

Non-Edible Vegetable Oils as Renewable Resources for Biodiesel Production: South-East Asia Perspective

Abstract: Biodiesel derived from plant species has been a major renewable source of energy and has received global interest mainly due to climate change issue. It has increasingly received worldwide attention as a promising alternative fuel. Growing interest in biodiesel production from edible oil brings scarcity in food supply. To overcome this problem, utilization of non-edible oils could be explored. Non-edible oil as biodiesel feedstock impressed in many factors such as energy sustainability and independence in cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Effect of different non edible inducer oil on lipase production was revealed that Honge oil was to induce higher lipase production than neem oil and palm oil as shown in Figure 4. Abul Kalam Mohammad Aminul Islam et al (33) reported in his studies that honge oil comprises higher amount of unsaturated fatty acids 70% among that 51% oleic acid compared to other non edible oils. Hence honge oil can be used as a inducer oil to enhance the lipase production, it was reported first in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of different non edible inducer oil on lipase production was revealed that Honge oil was to induce higher lipase production than neem oil and palm oil as shown in Figure 4. Abul Kalam Mohammad Aminul Islam et al (33) reported in his studies that honge oil comprises higher amount of unsaturated fatty acids 70% among that 51% oleic acid compared to other non edible oils. Hence honge oil can be used as a inducer oil to enhance the lipase production, it was reported first in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists and researchers are increasingly interested in the use of non‐edible candlenut oil as feedstocks to produce biofuel (biodiesel) owing to the relatively low cost, which lowers the price of biofuel 27 . Biodiesel fuel has many advantages and benefits over petro‐diesel fuel; nonetheless, it also has shortcomings and disadvantages 2,28‐40 . The major advantages of biodiesel are as follows: Biodiesel, as a renewable energy source, can support a continuous supply chain. Biodiesel is an environmentally friendly energy source that emits fewer greenhouse gases than diesel. The method of biodiesel production is simpler than that of petro‐diesel production. Biodiesel has a high cetane number, which promises effective engine performance and a longer engine lifespan with less maintenance. No additional lubricant is needed with biodiesel. Biodiesel fuel has great value for stimulating sustainable rural development. Transportation energy security issues could be solved using biodiesel fuel. Biodiesel fuel can be locally produced, making it a cost‐effective energy source. Biodiesel properties, such as sulfur content, flash point, aromatic content, and biodegradability are superior to those of petro‐diesel. Biodiesel has a highly biodegradable molecular structure with minimal combustion toxicity. Biodiesel is safer to handle and transport and less toxic. Biodiesel is more portable renewable fuel with more available combustion efficiency. Biodiesel is non‐corrosive and produced under low pressure and temperature conditions. Biodiesel is neither flammable nor toxic and reduces tailpipe emissions, visible smoke, noxious fumes, and odors. Biodiesel is a potential substitute for diesel in boilers or internal combustion engines and requires no major alterations. Biodiesel oxygen content is higher, which assists complete fuel combustion and decreases emissions. Cultivation of biodiesel materials in rural areas and unused land within numerous countries can notably increase national economic potential and reduce dependency on crude oil imports. …”
Section: Biodiesel: Advantages and Limitationsmentioning
confidence: 99%
“…27 Biodiesel fuel has many advantages and benefits over petro-diesel fuel; nonetheless, it also has shortcomings and disadvantages. 2,[28][29][30][31][32][33][34][35][36][37][38][39][40] The major advantages of biodiesel are as follows:…”
Section: Biodiesel: Advantages and Limitationsmentioning
confidence: 99%
“…The production potential of mahua seed is about 60 MT per annum. The current estimated production of mahua seed oil is 1.8 MT per year [5,6]. mahua oil has a specific gravity that is 9.11% greater than diesel.…”
Section: Introductionmentioning
confidence: 99%